Botbāt kh̨̄ong ʻongk̨̄on phatthanā ʻēkkachon dān kānphatthanā thēknōlōyī kānkasēt læ kānphatthanā chumchon nai chonnabot - Watthanā Wongkīattirat (Sathāban Wičhai Sangkhom, Čhulālongk̜̄on Mahāwitthayālai, 1995)
Development of Thai local communities by private development organizations.